KEGAGALAN MASUK PERGURUAN TINGGI NEGERI DALAM PERSPEKTIF ISLAM DAN SOSIAL KEMASYARAKATAN - Nasywa Safira Arsyi Putri; Rosi Khunal Khayati Nasywa; Safira Arsyi Putri (Universitas Hamzanwadi, 2021)
Face failure, stay positive, and don't assume failure is the end of everything. The objectives are, how to overcome and prevent the impact of failure based on the Qur'an, how to change the concept of failure based on the Qur'an, and how to rise from failure by drawing closer to Allah SWT. The research method uses Naturalistic research, which is about how to apply the knowledge of the Qur'an from the perspective of Failing to Enter the Dream College. The results show that Islam has a favorable view of the concept of failure, all of which are contained in the Al-Quran and Hadith; This indicates that as a Muslim believer we must always try and never give up because as has been explained that there are so many instructions and advice about the perspective of failure in the Al-Quran and Hadith.